2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176185
|View full text |Cite
|
Sign up to set email alerts
|

A "Verbal Thermometer" for Assessing Neurodegenerative Disease: Automated Measurement of Pronoun and Verb Ratio from Speech

Abstract: Clinicians often use speech to characterize neurodegenerative disorders. Such characterizations require clinical judgment, which is subjective and can require extensive training. Quantitative Production Analysis (QPA) can be used to obtain objective quantifiable assessments of patient functioning. However, such human-based analyses of speech are costly and time consuming. Inexpensive off-the-shelf technologies such as speech recognition and part of speech taggers may avoid these problems. This study evaluates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Identification and stratification into clinical trials at the very earliest stage of disease will be vital if treatments are to be effective. The use of ecologically relevant measures that quantify aspects of speech output have garnered recent interest in terms of both diagnosis and disease tracking from early stages [30][31][32][33], leading to the suggestion that automated analysis of speech might be used as a 'verbal thermometer' for PPA and FTD [34]. There is also considerable interest in the use of 'wet biomarkers' in measuring disease burden and intensity.…”
Section: The Challenge Of Clinical Prognosis: Assessing Disease Stagementioning
confidence: 99%
“…Identification and stratification into clinical trials at the very earliest stage of disease will be vital if treatments are to be effective. The use of ecologically relevant measures that quantify aspects of speech output have garnered recent interest in terms of both diagnosis and disease tracking from early stages [30][31][32][33], leading to the suggestion that automated analysis of speech might be used as a 'verbal thermometer' for PPA and FTD [34]. There is also considerable interest in the use of 'wet biomarkers' in measuring disease burden and intensity.…”
Section: The Challenge Of Clinical Prognosis: Assessing Disease Stagementioning
confidence: 99%
“…talkbank.org/discourse/). For instance, a recent study by Jarrold et al (2020) has shown that automated analysis could robustly measure pronoun and verb ratios in neurodegenerative populations, two measures present in the QPA.…”
Section: Discussionmentioning
confidence: 99%
“…A staging system for PPA could provide a bridge to the development of bespoke functional scales of daily life communication 77 that could in turn serve as outcome measures for clinical trials in these syndromes and language-led AD clinical phenotypes 78 . Looking forward, we envisage that particular symptoms identified as harbingers of early-stage PPA might inform the development of diagnostic 'cognitive stress tests' based on the analysis of patients' spontaneous conversation [79][80][81] or requiring production and/or understanding of speech in multi-talker environments or other demanding conditions 52,82 . However, the overriding value of a PPA staging system, as attested to in the qualitative analysis, will lie in the personalised care of individual patients and families navigating these illnesses -to help them signpost their journey, harness all appropriate supports and treatments, and plan for the future.…”
Section: Discussionmentioning
confidence: 99%